2018
DOI: 10.3389/fimmu.2018.02299
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus Type 1.3 Lena Triggers Conventional Dendritic Cells 1 Activation and T Helper 1 Immune Response Without Infecting Dendritic Cells

Abstract: Porcine Reproductive and Respiratory Syndrome virus (PRRSV) is an arterivirus responsible for highly contagious infection and huge economic losses in pig industry. Two species, PRRSV-1 and PRRSV-2 are distinguished, PRRSV-1 being more prevalent in Europe. PRRSV-1 can further be divided in subtypes. PRRSV-1.3 such as Lena are more pathogenic than PRRSV-1.1 such as Lelystad or Flanders13. PRRSV-1.3 viruses trigger a higher Th1 response than PRRSV-1.1, although the role of the cellular immune response in PRRSV cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 52 publications
10
55
1
Order By: Relevance
“…Moreover, CD172a + /CD163 − /MHC-II + and CD172a − /CD163 − / MHC-II + cells exhibit strong migration and antigenpresenting capabilities [10], which can be credited to the increased influx of these cells into the lungs during the course of infection. Our results were in agreement with those obtained in previous studies, which found that the populations of these cells are increased in the BAL after PRRSV-1 infection [8]. Interestingly, cDC1s activate allogenic naïve T cells and aid induction of the Th1 response, whereas cDC2s induce a Th2 response in pigs [10].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, CD172a + /CD163 − /MHC-II + and CD172a − /CD163 − / MHC-II + cells exhibit strong migration and antigenpresenting capabilities [10], which can be credited to the increased influx of these cells into the lungs during the course of infection. Our results were in agreement with those obtained in previous studies, which found that the populations of these cells are increased in the BAL after PRRSV-1 infection [8]. Interestingly, cDC1s activate allogenic naïve T cells and aid induction of the Th1 response, whereas cDC2s induce a Th2 response in pigs [10].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, dissecting how these immune cells respond to PRRSV infection is important to better understand the nature of PRRS. Until now, limited studies have investigated the alterations in the respiratory DC/macrophage network in pigs during disease progression [8,10], and the association of the alteration in this immune network with the T-cell response has not been reported. Here, we attempted to explore the dynamics of this important host defence mechanism in relation to PRRSV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ITGAX (CD11c) was highly expressed on macrophages as well, but lower on the putative cDC1, cDC2, and CD14 + DCs. This is contrary to the result of pig blood cDCs ( 22 ) but somewhat consistent with the analysis of lung DCs ( 28 ).…”
Section: Resultssupporting
confidence: 87%